The promised Neverland. Volume 14, Encounter - Shirai, Kaiu (Shonen Jump manga., 2021)
"The children of the Grace Field House orphanage must escape a macabre fate before it's too late. Life at Grace Field House is good for Emma and her fellow orphans. While the daily studying and exams they have to take are tough, their loving caretaker provides them with delicious food and plenty of playtime. But perhaps not everything is as it seems... In order to save a dying family member, Emma leads a small group of children into a demon farm in order to steal some medicine. This risky mission will require smarts, stealth and a bit of luck. Meanwhile, a mysterious group of humans is destroying the farms one by one. What is their secret?" --